1992
DOI: 10.1016/0014-5793(92)80627-s
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Ca2+ signaling pathways converge on CaM kinase in PC12 cells

Abstract: The role of multifunctional Ca2+/calmodulin‐dependent protein kinase (CaM kinase) in mediating various Ca2+ signaling pathways was examined in PC12 cells. Conversion of the kinase to a Ca2+‐independent form was used to monitor which neurotransmitters activate the enzyme in situ. CaM kinase responds to Ca2+ influx elicited by ligand‐gated Ca2+ channels for ATP and acetylcholine. It also responds to Ca2+ mobilization ofIP3‐sensitive stores elicited by phospholipase C‐linked receptors for ATP and acetylcholine as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Recent findings suggested that ␣7-nAChRs activation led to the neuroprotection against glutamate neurotoxicity via the Ca 2ϩ -dependent phosphatidylinositol 3-kinase pathway, and that nicotine protected neurons by activating phosphatidylinositol 3-kinase, which activated Akt and up-regulated Bcl-2 (Kihara et al, 2001). Furthermore, Ca 2ϩ influx through ␣7-nAChRs could activate Ca 2ϩ /calmodulin-dependent protein kinase-2 in PC12 cells (MacNicol and Schulman, 1992), resulting in nitric-oxide synthase-1 inactivation by its phosphorylation (Nakane et Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggested that ␣7-nAChRs activation led to the neuroprotection against glutamate neurotoxicity via the Ca 2ϩ -dependent phosphatidylinositol 3-kinase pathway, and that nicotine protected neurons by activating phosphatidylinositol 3-kinase, which activated Akt and up-regulated Bcl-2 (Kihara et al, 2001). Furthermore, Ca 2ϩ influx through ␣7-nAChRs could activate Ca 2ϩ /calmodulin-dependent protein kinase-2 in PC12 cells (MacNicol and Schulman, 1992), resulting in nitric-oxide synthase-1 inactivation by its phosphorylation (Nakane et Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Cells washed once with cold Tris-buffered saline plus 1 mM EDTA. Cell lysates were made by resuspending the cell pellet in homogenization buffer (20 mM Tris-HCl, pH 7.5, 0.5 mM EGTA, 1 mM EDTA, 10 mM sodium pyrophosphate, 0.4 mM sodium molybdate, 2 mM dithiothreitol, 0.5% Triton X-100, and protease inhibitors) (50). Cells were kept on ice 10 min with vortexing and then sonicated for 15 s. Total CaM kinase activity in 15 g of sample was assayed by phosphorylation of the CaM kinase-selective substrate syntide-2 (Pro-Leu-AlaArg-Thr-Leu-Ser-Val-Ala-Gly-Leu-Pro-Gly-Lys-Lys, 40 M), in the presence of Ca 2ϩ (0.5 mM) and calmodulin (1.5 g/assay tube) with 5 Ci/ assay tube [␥-…”
Section: Methodsmentioning
confidence: 99%
“…For these cells, it has been reported previously that ionomycin is able to activate CaM-KII, a kinase that requires CaM to be activated (64). Thus, we have monitored the activation of CaM-KII induced by ionomycin in the presence of different W13 concentrations.…”
Section: Functional Inhibitors Of Cam Prevent the Activation Of The Ementioning
confidence: 99%